HEDGES co-prevents both SARS-CoV-2 and pandemic influenza infection in mice by rapid, durable co-production of twelve different anti-pandemic monoclonal antibodies - Marissa Mack; Alice Ye; Sarah Ursu; Ryan Ice; Liliana Soroceanu; Stan Shoor; Sean McAllister; Tim Heath; Chakkrapong Handumrongkul; Robert Debs (PLoS ONE, 2026)
Despite all currently available anti-pandemic monoclonal-antibodies (mAbs) and vaccines, subsequently emerging pandemic-infections will likely become more pan-resistant-, -transmissible and/or -lethal. We have created HEDGES generation-2, a significantly more-combinatorial, -synergistic version of our generation-1 HEDGES DNA vector-based platform. We previously published that one safe intravenous injection of a HEDGES generation-1 DNA vector encoding one of three different FDA-approved mAbs produced durable therapeutic serum mAb levels as well as critical therapeutic endpoints in immunocompetent mice. Here we show one safe, intravenous administration of a 2 nd -generation HEDGES DNA vector co-encoding four different anti-SARS-CoV-2 mAbs rapidly then durably co-produces high anti-SARS-CoV-2 mAb serum levels that effectively block SARS-CoV-2 virus binding to the ACE-2 spike protein in immunocompetent mice. In addition, four weekly intravenous HEDGES generation-2 DNA vector administrations co-encoding a total of ten-different anti-SARS-CoV-2 mAbs, 5J8, plus an anti-1918 pandemic influenza mAb and mepolizumab, an FDA-approved anti-IL-5 mAb, durably co-produce highly-neutralizing 5J8 anti-pandemic influenza mAb serum levels, as well as durably block SARS-CoV-2 virus-ACE-2 receptor binding in mice. Furthermore, unlike vaccines and mAbs, HEDGES does not require an intact cold chain and is readily freeze dried, enabling its prolonged storage at ambient temperatures worldwide, even in equatorial regions. Also, HEDGES can create, then deploy novel, more effective anti-pandemic mAbs ~three weeks after their identification. Conversely, vaccines require ~three months to deploy, recombinant-mAbs ~nine months. By rapidly then durably co-producing many different highly-neutralizing, highly-synergistic anti-pandemic mAbs, HEDGES may effectively co-prevent both SARS-CoV-2 and pandemic-influenza infections. HEDGES may also prevent even more-transmissible, -pan-resistant and/or -lethal pandemic diseases that subsequently-emerge.